Role of Blind Closed Pleural Biopsy in the Management of Pleural Exudates - Marco F Pereyra; Esther San-José; Lucía Ferreiro; Antonio Golpe; José Antúnez; Francisco-Javier González-Barcala; Ihab Abdulkader; José M Álvarez-Dobaño; Nuria Rodríguez-Núñez; Luis Valdés (Canadian Respiratory Journal)
INTRODUCTION: The performance of blind closed pleural biopsy (BCPB) in the study of pleural exudates is controversial.